2018
DOI: 10.3390/nu10101438
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Content in Breast Milk and Its Association with Maternal Diet

Abstract: Background: Zinc is an indispensable element, being involved in many biological processes. Correspondingly, insufficient zinc intake in early youth can detrimentally affect the function of a growing body. The aim of this study was to determine zinc content in breast milk among lactating women in Latvia and factors (maternal diet; mother’s and baby’s characteristics; breastfeeding pattern) affecting it. Methods: In total, 62 mature milk (at least one month postpartum) samples were collected and pooled within 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 28 publications
2
22
0
2
Order By: Relevance
“…In our study, the majority of participants (63%, n = 20) did not reach the EAR value for zinc (10.4 mg/d). These results are consistent with previous studies that indicated that maternal dietary zinc intake was nearly or below the recommended values [ 38 , 39 , 40 ]. Data from several developing countries where zinc intake was presumed to be low (e.g., Bangladesh [ 53 ], Egypt [ 54 ], and Nigeria [ 55 ]), showed that HM zinc concentrations were relatively lower than those of well-nourished American women [ 56 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, the majority of participants (63%, n = 20) did not reach the EAR value for zinc (10.4 mg/d). These results are consistent with previous studies that indicated that maternal dietary zinc intake was nearly or below the recommended values [ 38 , 39 , 40 ]. Data from several developing countries where zinc intake was presumed to be low (e.g., Bangladesh [ 53 ], Egypt [ 54 ], and Nigeria [ 55 ]), showed that HM zinc concentrations were relatively lower than those of well-nourished American women [ 56 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the concentration of HM iron (0.33 mg/L) was higher compared to mature milk from Swedish (0.29 mg/L [ 34 ]), Honduran (0.21 mg/L [ 36 ]), Indonesian (0.26 mg/L [ 37 ]), Thai (0.19 mg/L [ 38 ]), and lower than Vietnamese (0.59 mg/L [ 39 ]) and Iranian (0.89 mg/L [ 24 ]) mothers. Regarding zinc, in our study its median concentration (2.12 mg/L) was similar or slightly higher than that reported in other countries [ 37 , 38 , 39 , 40 ]. Some of the divergences between the findings for HM iron and zinc concentrations may be related to the fact that iron content in HM was reported to be higher at the nighttime feeding and in hindmilk samples [ 27 ].…”
Section: Discussionsupporting
confidence: 82%
“…The content of some nutrients in breast milk is dependent on maternal dietary intake, including fatty acid profile [15], iodine [16] and vitamins B 1 , B 2 , B 6 and B 12 [17]. However, maternal dietary intake has a limited influence on breastmilk macronutrient composition [14] and some micronutrients, e.g., folic acid [17] and zinc [18]. Some studies have indicated that maternal nutritional status measured as body mass index (BMI) may influence the milk fat concentrations [14] as well as carotenoid concentrations [19].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc and iron concentrations in breast milk are high during early lactation and gradually decline thereafter [17][18][19]. The amounts of zinc and iron in breast milk consumed by infants after 6 months are lower than the estimated daily requirements [20,21]. The majority of zinc and iron intakes in infants during this period need to be provided by complementary foods.…”
Section: Introductionmentioning
confidence: 98%